Pengaruh Terpaan Kampanye No Plastic Straw dan Tingkat Kesadaran Lingkungan terhadap Perilaku Pengurangan Penggunaan Sedotan Plastik Pada Generasi Z - Arsya Yanuar Widyati; Yanuar Luqman; Muhammad Bayu Widagdo (Interaksi Online, 2022)
Excessive plastic straws use has a bad impact on the environment. No Plastic Straw is a campaign to reduce the use of plastic straws and minimize plastic straw waste. The purpose of the study was to determine the influence of No Plastic Straw Campaign Exposure, Environmental Awareness Level, and Reducing Plastic Straws Use Behavior in Generation Z. The theory used was Cognitive Response Theory and Value-Belief-Norm Theory. The sampling technique used non-probability sampling as many as 70 people with the criteria of female/male, aged 18-27 years, living in Semarang city, actively accessing social media, and having read, seen, or heard of No Plastic Straw Campaign. This study was tested using simple linear regression analysis. The result of the study was No Plastic Straw Campaign has no influence on the reducing plastic straws use behavior in Generation Z with a significant value of 0.521 and a regression coefficient of 0.054. Meanwhile, the results showed that the level of environmental awareness had an influence on reducing plastic straws use behavior in Generation Z with a significant value of 0.036 and a regression coefficient value of 0.121. So the Cognitive Response Theory is not proven in this study, while the Value-Belief-Norm Theory can be proven in this study.